Development of Optimum Design B-Series Propeller with Engine Propeller Matching, A Case Study 60-Meters Patrol Boat - Cahya Kusuma; I Made Ariana; Wibowo Harso Nugroho; Mahendra Indiaryanto; Baharuddin Ali (Institut Teknologi Sepuluh Nopember, 2022)
in preliminary ship design and ship propulsion systems, it is important to have a simple method of determining the optimization of the propeller diameter and propeller efficiency, as the minimum input data to arrive at a rough estimate of performance. This problem can be solved using propeller diagrams of the open water test series or polynomial regression. This research will introduce an optimization method for the design of the B series. The propeller design process, which was carried out as a single objective function using the MatLab code numerical method, encountered problems due to cavitation, required propeller thrust and engine propeller matching. Engine propeller matching is the matching of engine power, the hull and the propeller to achieve design speed with optimal efficiency. This research focus on case study results of testing a patrol boat with a length of 60 m. By using a computer program, this 60m patrol boat is able to reach a speed of 23.5 knots using a B5-92 and an engine power of 2935 kW with an efficiency of 64.2%. Using the DESPPC program, the 60m patrol boat is able to reach a speed of 23.5 using a B5-989 and an engine power of 2927 kW with an ETA-O efficiency of 64.5%. It can be concluded that the small computer program can be used as a B-Series propeller optimization method. For future research, this method will be developed for the other series based on polynomial regression such as Gawn series and Kaplan series.